The SET HASDM Density Database - W. Kent Tobiska; Bruce R. Bowman; S. David Bouwer; Alfredo Cruz; Kaiya Wahl; Marcin D. Pilinski; Piyush M. Mehta; Richard J. Licata (Space Weather)
Abstract The SET HASDM density database is available for scientific studies through a SQL database with open community access. The information in the SET HASDM density database covers the period from January 1, 2000 through December 31, 2019. Data records exist every 3 h during solar cycles 23 and 24. The database has a grid size of 10° × 15° (latitude, longitude) with 25 km altitude steps between 175 and 825 km. A description of the source of the database, its validation, its information content, and its accessibility are provided.